Causal association of sarcopenia with hepatocellular carcinoma risk in European population: a Mendelian randomization study - Cao, Jiali; Huang, Yumei; Zhu, Mengpei; Wang, Ziwen; Jin, Ze; Xiong, Zhifan (Frontiers in Nutrition, 2024)
Background: The causal association of sarcopenia with the incidence risk of hepatocellular carcinoma (HCC) in the European population, and the potential mediating role of C-reactive protein (CRP), remained unclear. This study employed a bidirectional two-sample, two-step Mendelian randomization (MR) analysis to investigate the causality and identify the mediator. Methods: Summary statistics for HCC, CRP, and sarcopenia-related traits, including appendicular lean mass (ALM), hand grip strength (HGS), and walking pace (WP), were acquired from publicly available databases. We conducted bidirectional MR and Steiger tests of directionality to check the presence of reverse causality. Besides, a two-step MR analysis was used to assess the mediating effect of CRP in the causality between sarcopenia and HCC. Tests for heterogeneity and horizontal pleiotropy were performed. Results: As ALM increases, the risk of HCC occurrence decreases (odds ratio (OR), 95% confidence interval (CI): 0.703, 0.524-0.943; P = 0.019). And, genetically predicted low-HGS (OR, 95%CI: 2.287, 1.013-5.164; P = 0.047) was associated with an increased incidence risk of HCC, with no reverse causality. However, we found no evidence supporting a causality between WP and HCC. CRP was identified as the mediator of the causal effect of ALM and low-HGS on HCC, with corresponding mediating effects of 9.1% and 7.4%. Conclusions: This MR study effectively demonstrates that lower ALM and low-HGS are linked to an elevated risk of HCC within the European population, and the causality was not bidirectional. Furthermore, CRP serves as a mediator in the associations. These findings may help mitigate HCC risk among individuals with sarcopenia.